PENGARUH PENGELOLAAN KELAS DAN MANAJEMEN WAKTU TERHADAP MOTIVASI BELAJAR SISWA DI SMK KARTIKA 1-2 PADANG - Wulandari, Winda; Oknaryana, Oknaryana (Penerbit Lafadz Jaya, 2025)
This study aims to determine and analyze 1) the effect of classroom management and time management on the learning motivation of students at SMK Kartika 1-2 Padang. 2) the effect of classroom management on the learning motivation of students at SMK Kartika 1-2 Padang. 3) the effect of time management on the learning motivation of students at SMK Kartika 1-2 Padang. This type of research is classified as quantitative research. The sampling technique used was cluster area sampling, with 90 samples, because the population was too large, which was more than 100. The data collection technique used a questionnaire compiled using a Likert scale. The trial of this research instrument used validity and reliability tests. The data analysis techniques used were descriptive analysis, inductive analysis, and multiple regression analysis. Hypothesis testing used was the F Test and t Test using the SPSS program. The results of this study indicate that 1) classroom management and time management have a positive and significant effect on the learning motivation of students at SMK Kartika 1-2 Padang. 2) Class management does not have a positive and significant effect on the learning motivation of students at SMK Kartika 1-2 Padang. 3) Time management has a positive and significant effect on the learning motivation of students at SMK Kartika 1-2 Padang.